Capital management and budgeting in the public sector - Srithongrung, Arwiphawee; Ermasova, Natalia; Yusuf, Juita-Elena Wie, 1976- (IGI Global, 2019)
"This book addresses the topic of capital management and budgeting in the public sector, with a focus on capital management and budgeting processes. It focuses on how capital management and budgeting processes support effective investment in public infrastructure, particularly as viewed through a normative framework"--